2011
DOI: 10.3350/kjhep.2011.17.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Optimal technique and response of doxorubicin beads in hepatocellular cancer: bead size and dose

Abstract: Background/AimsIt has been shown that the drug-eluting beads loaded with doxorubicin (DEBDOX) are effective for the treatment of hepatocellular carcinoma (HCC). However, the optimal safety and efficacy still remain to be established by using various bead sizes, doxorubicin doses, and the degree of stasis.The aim of this study was to determine the optimal safety and efficacy of DEBDOX in the treatment of HCC.MethodsAnalysis of a 503-patient prospective, multicenter, multinational Bead Registry Database from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Third, efficacy (response rate) was not recorded; this was an intentional omission because the present study was not designed to assess response in view of the obvious selection bias of the patient study population and the intrinsic limitations in finding a control group. Finally, the assessment of the degree of stasis of the selected vessels could potentially provide some relevant association with the incidence of LBI, as previously reported (4). Because of the lack of consensus on how to assess the degree of stasis of a treated vessel and the retrospective nature of our study, this variable was not incorporated in the analysis.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Third, efficacy (response rate) was not recorded; this was an intentional omission because the present study was not designed to assess response in view of the obvious selection bias of the patient study population and the intrinsic limitations in finding a control group. Finally, the assessment of the degree of stasis of the selected vessels could potentially provide some relevant association with the incidence of LBI, as previously reported (4). Because of the lack of consensus on how to assess the degree of stasis of a treated vessel and the retrospective nature of our study, this variable was not incorporated in the analysis.…”
Section: Discussionmentioning
confidence: 75%
“…Despite the reported benefits, fundamental questions remain with respect to optimal particle size and type and chemotherapeutic dose for clinical use (3,4). Existing data regarding the use of particles sized 100–300 μm, 300–500 μm, and 500–700 μm show adverse event (AE) rates ranging from 10% to 58%, with fewer AEs occurring with the use of smaller particles (46).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The data from a prospective, non-controlled, repeat treatment registry of 206 patients undergoing 343 treatments for HCC indicated that smaller beads offer the opportunity for repeated treatments, a larger cumulative dose delivery, a lesser degree of complete stasis, and fewer adverse events. [ 58 ] The recommended treatment dose range reported by the PRECISION study[ 47 ] is 100-150 mg per patient, which was shown to be safe and effective even at the highest dose. [ 46 ] Dose adjustments for bilirubin levels may also be used, as in Varela et al .…”
Section: Chemoembolizationmentioning
confidence: 99%
“…Better tumour penetration of small (100-300 μm) versus larger (300-500 μm) microspheres has been demonstrated in VX2 liver tumour. 62 Potential benefits of small microspheres have been reported in a prospective multi-institutional non-randomised registry for HCC patients 63 and are also suggested for hmCRC patients. [64][65][66][67] In a recent study, increased benefit with decreased size has been shown, with an approximately twofold improved drug coverage in swine kidney (70-150 μm versus 100-300 μm).…”
Section: Tandem™ -The Next Step In Drug-eluting Beads Technologymentioning
confidence: 99%